Synergizing digitalization and sustainability in tourism: Impacts, implications, and pathways - Gunawan Bata Ilyas; Hanugerah Kristiono Liestiandre; Yanti Mayasari Ginting; Siti Aysah; Nanoe Rolin Prasetyo (Journal of Enterprise and Development (JED), 2023)
Purpose — This research article examines the intricate interplay between digitalization and sustainability in the context of the tourism industry. The purpose of this study is to explore how the integration of digital technologies can enhance sustainable practices within the tourism sector while also identifying potential challenges. Method — The research methodology involves a combination of literature review, case studies, surveys, and interviews to provide a comprehensive analysis of the subject.Result — The research findings highlight the transformative impact of digitalization on the tourism experience. Online platforms and mobile applications have revolutionized travel planning and personalized itineraries, while also fostering a growing awareness of sustainability among tourists. Through case studies, successful instances of the harmonious convergence of digitalization and sustainability are presented, showcasing innovative approaches to destination management, energy efficiency, and community engagement.Contribution — The research informs stakeholders, offering a roadmap for responsible, tech-enhanced tourism. It emphasizes balanced personalization, cultural preservation, stakeholder collaboration, digital literacy, and equitable access to digital tourism benefits.